Experiência de um aluno de Medicina Veterinária na comunidade de Santa Maria do Cambucá-Pernambuco, em programa de extensão universitária - Carvalho, Yuri Karaccas de [UNESP] (Universidade Estadual Paulista (Unesp), 2004)
The Universidade Solidária program (UNISOL), involves educational actions by university students in poor communities. The city of Santa Maria do Cambucá, PE was chosen by UNISOL – UNESP. According to data, the occurrence of cases of human diseases in the city is very high. Thus, a questionnaire was put together in order to try to relate the population habits to the commonest diseases. Forty-five people, of different ages and professions, were interviewed. The analysis of the results showed some knowledge of the population about health aspects. Based on the analysis and on the observed local reality, some changes were proposed which may decrease the incidence of diseases. UNISOL is an important opportunity for the target population to have contact with modern science applied to the resolution of local problems. The students who participate in this educational action acquire a valuable life experience as well as a deeper vision of the Brazilian social reality; in addition, they also enhance their creativity and leadership. This experience is a valuable contribution to their civic conscience as it provides opportunities for social interaction and understanding of the social problems of the country.

O programa Universidade Solidária (UNISOL), destina-se a atividades educativas de estudantes universitários em comunidades carentes. O município selecionado pelo UNISOL/UNESP foi Santa Maria do Cambucá - PE. Segundo dados locais, as porcentagens de casos humanos de doenças descritos no município são elevadas. Sendo assim, aplicou-se um questionário relacionando os hábitos da população e as doenças mais freqüentes, onde foram entrevistadas 45 pessoas, com diferentes profissões e idades. A análise do questionário revelou algum grau de conhecimento e comprometimento da comunidade com alguns aspectos de saúde. Baseado na análise do questionário e na realidade local foram propostas mudanças, visando a diminuição da ocorrência de doenças. O UNISOL é uma grande oportunidade para a comunidade entrar em contato com a vanguarda das ciências aplicadas na resolução de problemas locais. Em contrapartida, os estudantes, nesta atividade de cunho educativo, adquirem uma valiosa experiência de vida e uma visão mais apurada da realidade brasileira, desenvolvendo a criatividade e a liderança jovem, contribuindo assim para a formação cidadã, com condições de maior interação social e de entender os graves problemas sociais do país.
Experience of a veterinary medicine student in the community of Santa Maria do Cambucá, Pernambuco, in an extension program
Keywords: Health education; University extension; UNISOL; Biológicas; Agrárias e veterinárias; Educação; Extensão; Saúde; Veterinária; UNISOL